Future perspectives for advancing regulatory science of nanotechnology-enabled health products - Blanka Halamoda-Kenzaoui; Robert Geertsma; Joost Pouw; Adriele Prina-Mello; Moreno Carrer; Matthias Roesslein; Adrienne Sips; Klaus Michael Weltring; Kathleen Spring; Susanne Bremer-Hoffmann (Drug Delivery and Translational Research, 2022)
The identification of regulatory challenges for nanotechnology-enabled health products, followed by discussions with the involved stakeholders, is the first step towards a strategic planning of how such challenges can be successfully addressed in the future. In order to better understand whether the identified regulatory needs are sector-specific for health products or might also hinder the progress in other domains, the REFINE consortium reached out to communities representing other sectors that also exploit the potential of nanotechnology, i.e. industrial chemicals, food and cosmetics. Through a series of trans-sectorial workshops, REFINE partners identified common as well as sector-specific challenges and discussed possible ways forward. Potential solutions lie in a more strengthen collaboration between regulatory and research communities resulting in a targeted production and exploitation of academic data for the regulatory decision-making. Furthermore, a coordinated use of knowledge sharing platforms and databases, trans-sectorial standardisation activities and harmonisation of regulatory activities between geographical regions are possible ways forward, in line with the upcoming European political initiatives such as the Chemical Strategy for Sustainability (CSS). Finally, we also discuss the perspectives for further development and sustainability of methods and tools developed in the REFINE project. Graphical abstract